An exploratory study of the experiences of deceased‐donor liver transplant recipients and their need for psychotherapeutic support. Issue 15 (17th May 2020) - McKie, Paul; Webzell, Ian; Tavabie, Oliver; Loewenthal, Del; Heaton, Nigel
Abstract: Aims and objectives: This study aimed to explore the experiences of liver transplant recipients during their journey through the treatment and their need for psychotherapeutic support related to this process. Background: Over time, measures of survival and quality of life in liver transplant recipients have continued to improve but their emotional needs remain under explored. In the longer‐term recovery from transplantation, the focus shifts from physical health to psychological health. In the UK, there are no known embedded adult psychological services in liver transplant centres to react to this need. Design: A qualitative descriptive design was used. Methods: Grounded theory analysis was used to study the narratives of six adult liver transplant recipients. Through a process of coding, conceptual categories were established to describe the participant experiences. The study adhered to the EQUATOR checklist, SRQR. Results: Four categories emerged that were related to the experience of liver transplantation for the recipients. These were a process of adjustment, the phenomenon of waiting, liver transplant as a transformative experience and on the value of support. The participants identified a lack of psychotherapeutic support provided by the liver transplant service and felt that an embedded psychotherapeutic service would promote accessing such support during challenging times. Conclusion: Through the process of liver transplantation, recipients experience challenges with adjustment, waiting, feeling transformed and they value support with these feelings. In correlation with other studies, the findings of this study highlight the need for providing psychotherapeutic support within liver transplant services. Relevance to clinical practice: The study provides evidence to support recommendations for a conjoined psychotherapy service within liver transplant services to support patients with their holistic needs.